Development of bio-based benzoxazines derived from agroindustrial residues for the production of high-performance polymers - Kotzebue, Lloyd Ryan Viana (2020)
Thermosetting resins are highly desired in polymeric composite applications, especially high-performance polymeric materials with high mechanical and thermal properties. Among the resins that fit these criteria, benzoxazine resin is conquering its space in the high-performance thermosetting resin arena due to the impressive thermal and mechanical properties of its polymer, polybenzoxazine, which can be higher than of the conventional thermosetting resins. As the high-performance and commercially available benzoxazine resins are based on the toxic bisphenol A (BPA), research has been performed on alternative starting materials for renewable high-performance benzoxazine resins. Looking forward to aligning benzoxazine chemistry with sustainability, this work focuses on developing bio-based benzoxazine resins in an eco-friendly manner, following as much as possible the principles of Green Chemistry. After the production of these resins, they were used to develop renewable high-performance thermosets. Chapter 1 and 2 provide the introduction and fundamental understanding of benzoxazine chemistry, thermosets, and the necessity to develop these two topics sustainably. Chapter 3 discusses the development of bio-based benzoxazine using lignocellulose derivates (catechol and furfurylamine) as starting materials by using an eco-friendly synthesis method, which compromises the use of microwave irradiation heating source and poly(ethylene glycol) as solvent. To validate this synthesis method for other benzoxazine monomers, a semi-bio-based benzoxazine was obtained using BPA and furfurylamine as starting materials. These two monomers were further copolymerized in different ratios into polybenzoxazines, demonstrating high thermal and mechanical properties, glass transition temperatures ranging from 290 to 350 oC, and good flame retardancies. Chapter 4 discusses the use of widely available renewable resources to develop high-performance and BPA free bio-based benzoxazine resins by using Cashew Nut Shell Liquid (CNSL) as starting material. The obtained resin was copolymerized with the previously lignocellulose-based benzoxazine in different ratios, demonstrating polybenzoxazines with higher glass transition temperatures and flame retardancies than the BPA-based benzoxazine resins.